Rhizobium leguminosarum Glutathione Peroxidase Is Essential for Oxidative Stress Resistance and Efficient Nodulation - Hu, Aiqi; Chen, Xiaohong; Luo, Sha; Zou, Qian; Xie, Jing; He, Donglan; Li, Xiaohua; Cheng, Guojun (Frontiers in Microbiology, 2021)
Glutathione (GSH) plays a tremendous role in regulating the homeostasis of redox state, and appears to be essential for proper development of the root nodules. Glutathione peroxidase (Gpx) catalyzes the reduction of peroxides by oxidation of GSH to oxidized GSH (GSSG), which can in turn be reduced by glutathione reductase (GR). However, it has not been determined whether the R. leguminosarum Gpx or GR is required during symbiotic interactions with pea. To characterise the role of glutathione-dependent enzymes in the symbiotic process, single and double mutants were made in gpxA (encoding glutathione peroxidase) and gshR (encoding glutathione reductase) genes. All the mutations did not affect the growth of R. leguminosarum, but they increased the sensitivity of R. leguminosarum strains to H2O2. Mutant in GpxA had no effect on intracellular GSH levels, but can increase the expression of the catalase genes. The gshR mutant can induce the formation of normal nodules, while the gpxA single and double mutants exhibited an abnormal nodulation phenotype coupled to more than 50% reduction in nitrogen-fixing capacity, these defects in nodulation were characterized by the formation of undeveloped and ineffective nodules. In addition, the gpxA and gshR double mutant was severely impaired in rhizosphere colonization and competition. LC-MS/MS analysis quantitative proteomics techniques were employed to compare differential gpxA mutant root bacteroids in response to the wild type infection. Twenty-seven differentially expressed proteins were identified including seven up-regulated and twenty down-regulated proteins. By sorting the down-regulated proteins according to metabolic function, eight proteins are transporter protein, seven proteins are dehydrogenases, deoxygenases, oxidase and hydrolase. Moreover, three down-regulating proteins are directly involved in nodule process.